(3OjhGf GHf YjSis - (3CHhHcQ jMji Hf eMeO GdLRGQ Hf YjSi GdSQbSWjs ((3CHhYHOGddg eMeO GdeaVd feQjW s)
(3ChdgG (B:s
(3hHYO(B: (3aEf GdTYQ deG cGf OjhGf GdYQH GdPj Hg MaXJ CSeGAgG hEfSGHgG hMbbJ Hg EfJeGAgG ddaVGFd hGfJSGHgG aEf GdCSJGP GHf YjSi GdSQbSWj deG NU ef GdTYQ s
(3BNQgG (B:s
(3eHJhQ hjfJgj CKfGA bUjOI jeOM HgG PG GdhRGQJjf CHG GdEUHZ hBNQ HjJ ehLhO(B: (3JbGS SGYI ajgG cjhe hef Whd GdoqSQi TgQG cYGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B60s
(3jdj GdOjhGf eLehYI cHjQI ef GdbUGFO dTYQGA eNJdajfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B166 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs